2003
DOI: 10.1002/mrm.10412
|View full text |Cite
|
Sign up to set email alerts
|

Muscle glycogenolysis is not activated by changes in cytosolic P‐metabolites: A 31P and 1H MRS demonstration

Abstract: Skeletal muscle contraction and glycogenolysis are closely coupled. The standard explanation for this coupling, as taught in modern biochemistry textbooks, is that the metabolic products of contraction (ADP, AMP, P i ) feed back to activate glycogenolytic enzymes, thus providing for resynthesis of ATP. However, both in vivo 31 P MRS analyses and chemical analyses of muscle extracts have provided results that are contrary to this theory, at least in its simplest form. The MRS studies suffer from ambiguous assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…The flux through these reactions is controlled, in part, by substrate availability of P i and allosteric regulation by free cytosolic AMP and ADP, which would both be expected to be elevated following high-intensity exercise. However, some studies (10,14,28,36) have observed no evidence of PCr recovery following exercise in ischemic conditions, suggesting that glycolytic flux terminates abruptly at the end of exercise and that factors more temporally coupled to muscle contraction, such as free cytosolic Ca 2ϩ , are required for activation of glycogenolysis/glycolysis. On the other hand, Crowther et al (4) observed that glycolytic flux remained high at end exercise for 3 s following ischemic exercise and de- Data are means Ϯ SE; n ϭ 10 humans; n ϭ 15 rats (n ϭ 7 low, 8 high).…”
Section: Discussionmentioning
confidence: 99%
“…The flux through these reactions is controlled, in part, by substrate availability of P i and allosteric regulation by free cytosolic AMP and ADP, which would both be expected to be elevated following high-intensity exercise. However, some studies (10,14,28,36) have observed no evidence of PCr recovery following exercise in ischemic conditions, suggesting that glycolytic flux terminates abruptly at the end of exercise and that factors more temporally coupled to muscle contraction, such as free cytosolic Ca 2ϩ , are required for activation of glycogenolysis/glycolysis. On the other hand, Crowther et al (4) observed that glycolytic flux remained high at end exercise for 3 s following ischemic exercise and de- Data are means Ϯ SE; n ϭ 10 humans; n ϭ 15 rats (n ϭ 7 low, 8 high).…”
Section: Discussionmentioning
confidence: 99%
“…This may partly reflect the fact that lactate efflux is favoured in isolated muscle preparations that are perifused with lactate-free solution (Boutilier et al, 1986). However, the chief reason seems to be that glycolytic activation is minimal in non-contracting anoxic muscle (Hsu and Dawson, 2003). Interestingly, Vezzoli et al (Vezzoli et al, 2004) observed that the time course of suppression of ATP synthesis rate was essentially paralleled by changes in the phosphocreatine (PCr) breakdown rate, perhaps indicating that anaerobic energy turnover in resting and/or hypometabolic muscle is controlled to a large extent by ATP supply from PCr hydrolysis.…”
Section: Room Temperature Anoxic Responsesmentioning
confidence: 99%
“…The time courses of liver glycogen depletion and the onset of muscle glycogenolysis are essentially mirrored by the rise in plasma lactate levels in the first few weeks of hypoxic submergence (Fig.·4). In isolated frog muscle, energy turnover during acute anoxia at 4°C is apparently supported entirely by PCr hydrolysis; glycolytic activation seems tightly coupled to the onset of increased contractions (Hsu and Dawson, 2003). The clear activation of muscle glycogenolysis in vivo may mean that some low level of muscular activity occurs continuously during the initial stages of hypoxic coldsubmergence and/or that circulatory factors are important for mobilising muscle glycogen.…”
Section: Hypoxia Responses During Cold-submergencementioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of a steady state, at work rates above oxidative capacity, PCr may become nearly depleted (5), whereas P i concentration can continue to increase because of further ATP hydrolysis. Although the direct effect of elevated P i concentration on glycogenolysis and glycolysis can be debated (8,18,32,38), higher cellular P i may also foster a greater rate of P i efflux (35) and induce a net loss of phosphate from the cell (14).…”
mentioning
confidence: 99%